Knowledge exchange types and strategies on the innovation interactions between KIBS firms and their clients in Taiwan - Tai-Shan Hu; Cheng-Wei Yu; Ping-Ching Chia (Cogent Business & Management, 2018)
This investigation discusses the innovative activities of Knowledge-Intensive Business Services (KIBS) in the developmental process. To improve understanding of KIBS, the study aims to understand empirically the functions and mechanisms of knowledge intermediaries in different organizations and developmental processes, and also explores knowledge exchange and factors affecting KIBS. This study performs an empirical analysis of KIBS based on a recent manufacturer survey and emphasizes the connections among KIBS, innovation and forms of knowledge. The research results indicate the following conclusions: (1) Taiwanese KIBS enterprises tend to exchange knowledge with clients through mixed and codified knowledge; (2) firms that rely mainly on the exchange of codified knowledge have improved connections with clients, technologies, research innovation and application of advanced technologies; (3) enterprises mainly exchange mixed knowledge, and focus on knowledge management and information sources required during innovation processes, and (4) fewer enterprises exchange knowledge through tacit knowledge. The research implication is that enterprises emphasize different factors based on different types of knowledge exchange and services.
Keywords: 650